Espectroscopia óptica: uma nova ferramenta na avaliação do vigor de sementes de Brachiaria - IZABELA CRISTINA DE OLIVEIRA (2021)
Seeds vigor is the reason for studies to characterize the ability of seeds to germinate and generate seedlings quickly even in adverse conditions, a result of genetic, physiological and agronomic attributes. However, the tests used to measure seed vigor are relatively time consuming, delaying decision making in relation to seed lots with greater probability of success in the field. Basead on technological and computational advances, Fourier transform infrared spectroscopic techniques (FTIR), associated with chemometric methods, presents itself as a tool to obtain information about seeds in a simple and fast way, accelerating the choice of the best seed lots to be planted. For the formation of pastures, the wide use of Brachiaria brizantha in particular the cultivars Marandu and Paiaguas, for a fees animal. Therefore, the study was investigate the applicability of FTIR spectroscopic techniques associated whith chemometric methods to asses the vigor of Brachiaria seed lots. Initially the the seeds were submitted to germination and vigor tests, obtain information about the physiological quality. Subsequently, seeds were evaluated using FTIR spectroscopic analysis, where the data were obtained by multivariate statistics, with the application of principal component (PCA) and Machine Learning. The spectra generated by the FTIR allowed the identification of the main molecules responsible for the differentiation between high and low vigor batches, while the analyzes were responsible flor reducing the dimensionality of the data and highlighting the main points of interest in thes study. Through the analyzes carried out, it was identified that in the spectrum ranges from 1800 to 1600 cm-1, proteins, lipids anda mines were classified, being these as the main molecules responsibles for the separation of lots of high and low vigor, both to cultivate Marandu, as for Paiaguás. The information obstained in this work is of paramount importance for assessing the vigor of Brachiaria seeds, with precision and in a much shorter time than standard laboratory tests. Thus, the use of FTIR spectroscopy is promising for assessing the physiological quality of Brachiaria seeds.